Biomechanical evaluation of fracture repair in dogs : An experimental study - Hilmi Farook Ali Ibrahim Harb; Abdelhalim Mohamed Elhabak; Inas Nabil Elhussieny; Mohamed Barakat Mostafa (Cairo : Hilmi Farook Ali Ibrahim Harb, 2010)
This study was carried to investigate the influence of mechanical tension and bending forces in the repaired femora after fixation wiith intramedullary pins bone plates and screws and external skeletal fixation devices on 27 adult male mongrel dogs in different ages and body weight . Clinical radiographic and biomechanical evaluation of repaired fractures were studied and compared with contra - lateral control limb
Thesis (M.Sc.) - Cairo University - Faculty of Veterinary Medicine - Department of Surgery - Anesthesiology and Radiology
Issued also as CD
Keywords: Fixation; Fracture; Repair